PENGARUH KERAPATAN TANAM DAN KONSENTRASI PUPUK NPK PADA KRISAN POT (Chrysanthemum morifolium Ramat) - Ramadhan, Feby Steviani; Setyono, Setyono; Nugroho, Evi Dwi Sulistya (JURNAL AGRONIDA, 2018)
Chrysanthemum is an ornamental plant that people likes, grows the whole year, and has high economic value.  This study was aimed at assessing the effects of planting density and  concentration ofNPK fertilizer on the growth of potted chrysanthemum.  The study was conducted in a plastic house at the Indonesian Ornamental Crops Research Institute (IOCRI), Cipanas, Cianjur, West Java from March to June 2017.  Shoot cuttings of ±7 cm of potted chrysanthemum of Avanthe Agrihorti cultivar were used.  A completely randomized design in a factorial pattern with factors was used.  The first factor was planting density and the second factor was concentrationof NPK (16:16:16) fertilizer.  The planting density consisted of 5, 6, and 7 shoot cuttings and concentrationof NPK fertilizer were 150, 200, 250, and 300 ppm.  Results showed that planting density significantly affected stem diameter, number of buds, and width of canopy.  No effect concentrationof fertilizer was found on all variables. Keywords: potted chrysanthemum, planting density, NPK fertilizer